Logistics Basics — Exercises — Case Studies - Gleissner, Harald; Femerling, J. Christian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
Logistics is the ideal book for Bachelor students of logistics, providing a solid foundation as well as a practical guide. In modular and clear form, it explains key concepts, principles, and practices of logistics. Learning objectives as well as several case studies are integrated into each chapter. It features chapters on Principles of Logistics; Logistics Systems; Transport Systems and Logistics Services; Warehousing, Handling and Picking Systems; Inventory, Stock and Provisioning Management; Logistics Network Planning; IT in Logistics; and Logistics Controlling. In addition, the second fully updated German edition has been extended by the chapters Logistics Infrastructure and Investment and Financing in Logistics. “This book offers, in a very clear and concise manner, access to fundamental management topics of modern logistics. Well-chosen case studies serve to illustrate best practice solutions.” Professor Peter Klaus, member of Logistics Hall of Fame ”This new textbook facilitates a comprehensive and easy-to-grasp insight into the complex subject area of logistics. The authors have succeeded in presenting a good mix of theoretical foundation and practical application. Due to its clear structure and extensive range of topics, this book is highly suitable not only for students, but also for practitioners.” Bernhard Simon, Managing Director, DACHSER GmbH & Co. KG.
Introduction -- The Principles of Logistics -- Logistics Systems -- Logistical Infrastructure -- Transport Systems and Logistics Services -- Warehousing, Handling, and Picking Systems -- Inventory, Stock, and Provisioning Management -- Logistics Network Planning -- IT in Logistics -- Investment and Financing in Logistics -- Logistics Controlling -- Business Models and Industry Solutions.
Keywords: Production management; Engineering economics; Engineering economy; Organization; Planning; Operations Management; Engineering Economics, Organization, Logistics, Marketing; Organization